Grafting Compatibility, Scion Growth, and Fusarium Wilt Disease Incidence of Intraspecific Grafted Tomato - Saman, Prakob; Kawicha, Praphat; Sangdee, Aphidech; Wongpakdee, Somporn; Rattanapolsan, Ladawan; Ponpang-Nga, Pancheewan; Suwor, Patcharaporn; Thanyasiriwat, Thanwanit (My University, 2022)
The tomato (Solanum lycopersicum L.) is one of the most important vegetables grown globally. However, the production of tomatoes is restricted by Fusarium oxysporum f. sp. lycopersici (Fol). This study aims to investigate the ability of Fol-resistant tomato genotypes to be a rootstock for the susceptible cultivar. In this study, a tomato cultivar was grafted on rootstocks of the same species (intraspecific), and grafting compatibility, peroxidase gene expression, and fusarium wilt disease incidence of tomato scion was evaluated. A Fol-susceptible tomato 'Sidathip 3' (SDT3) was grafted onto four different Fol-resistant tomato genotypes and compared with self-grafted cultivar/cultivar and rootstock/rootstock. The survival rate of all grafted plants was 100% at 20 days after grafting (DAG) without significant differences in incompatibility evaluated at 42 days after grafting. The expression of the peroxidase gene (Solyc02g084800.2) using the qPCR technique was compared in self-grafted rootstock LE472/LE472 and SDT3/LE472. The expression level was three times higher in heterografted plants than in self-grafted ones at 15 DAG, indicating graft incompatibility. The rootstocks did not affect the height of the plant, the number of branches, the size of the fruit, or the yield of SDT3 scion. All intraspecific heterografted plants significantly controlled Fol when evaluated 60 days after inoculation. These results showed the usefulness of intraspecific grafting by using the proper rootstock genotypes to increase pathogen resistance in addition to stimulating growth and fruit yield.
Keywords: Fol control; grafting compatibility; peroxidase; Solanum lycopersicum; tomato rootstock resistance